2018
DOI: 10.1007/s11205-017-1826-7
|View full text |Cite
|
Sign up to set email alerts
|

Wellbeing and Society: Towards Quantification of the Co-benefits of Wellbeing

Abstract: The objectives of this paper are twofold. First, it reviews the empirical evidence showing the existence of linkage between wellbeing and possible co-benefits, investigating in particular the positive effect that happiness and life satisfaction can have on health, social outcomes, employment, education and environmental behaviours. Second, it presents the valuation methods that have been proposed in the literature to place a monetary value on these outcomes. With wellbeing having become more and more relevant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 122 publications
(125 reference statements)
3
55
0
3
Order By: Relevance
“…In fact, some studies have shown a positive association between MD and quality of life in healthy adults [ 5 , 45 ], and an inverse association with depression risk, with significant dose–response relationships [ 17 , 46 ]. On the other hand, enhanced SWB has been linked to a better health status, and healthy behaviors [ 47 , 48 ]. Most of the performed studies were observational and focused on the hedonic dimension of well-being, showing that higher levels of life satisfaction and positive affect were correlated with a lower incidence of cardiovascular disease, diabetes, and cancer [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, some studies have shown a positive association between MD and quality of life in healthy adults [ 5 , 45 ], and an inverse association with depression risk, with significant dose–response relationships [ 17 , 46 ]. On the other hand, enhanced SWB has been linked to a better health status, and healthy behaviors [ 47 , 48 ]. Most of the performed studies were observational and focused on the hedonic dimension of well-being, showing that higher levels of life satisfaction and positive affect were correlated with a lower incidence of cardiovascular disease, diabetes, and cancer [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…They are also less likely to engage in criminal or delinquent activity [54]. The impact of general well-being on society is strong enough that Maccagnan, Wren-Lewis, Brown, and Taylor [55] suggest that it may be just as important to accurate assess and nurture the happiness of a society as it is to consider more traditional measures of a country’s success, such as its GDP (gross domestic product).…”
Section: Changing the World In New Waysmentioning
confidence: 99%
“…A number of these different perspectives have been employed by tourism researchers in their studies of both tourist and resident well-being (Hartwell et al, 2018;Uysal et al, 2016). While there is no theoretical consensus on how best to measure human well-being, it is widely agreed to be a multi-dimensional concept that incorporates notions of material comforts, individual freedoms, opportunities, mental states and capabilities (Durand, 2015;Helliwell et al, 2019;Maccagnan et al, 2019). Space limitations, however, preclude giving a comprehensive account of the different measures of wellbeing (but see Dodge et al, 2012;Newton, 2007).…”
Section: Dimensions Of Well-beingmentioning
confidence: 99%